Quality of life, cardiovascular disease and mortality in advanced chronic kidney disease - Hakamäki, Markus (fi=Turun yliopisto|en=University of Turku|, 2022)
Chronic kidney disease (CKD) patients suffer from impaired Health-related Quality of Life (HRQoL). Impaired HRQoL has important implications for their prognosis. Cardiovascular disease (CVD) is common in CKD patients, leading to excess morbidity and mortality in this population. Risk factors unique to the CKD population add to the traditional risk factors. A multi-faceted treatment approach to improve the HRQoL and prognosis of CKD patients is needed. Correctly assessing a patient’s prognosis would be helpful in tailoring treatment. A Chronic Arterial Disease, Quality of Life and Mortality in Chronic Kidney Injury (CADKID) Study enrolled 210 participants with advanced non-dialysis CKD. The cardiovascular system was assessed by exercise test, echocardiography, evaluation of abdominal aortic calcification (AAC) and vascular ultrasound. A wide selection of biomarkers and HRQoL were measured . HRQoL was associated with cardiac biomarkers, Troponin T (TnT), N-terminal Pro-B-type Natriuretic Peptide (proBNP) and echocardiographic measure of cardiac systolic function, global longitudinal strain (GLS). A measure of the physical aspect of HRQoL, Physical Component Summary, was associated with mortality. In the longitudinal study of HRQoL, kidney transplantation improved kidney disease-specific aspects compared to dialysis. Cardiovascular determinants of mortality in the CADKID study were TnT, proBNP, serum albumin, AAC, exercise performance and an echocardiographic measure of cardiac diastolic function, E/e’. The incidence and prevalence of atrial fibrillation in the study cohort were high. Age, elevated TnT and increased left atrial volume index were associated with the incidence of atrial fibrillation. HRQoL is associated with biochemical and echocardiographic markers of cardiac function. Kidney transplantation is the renal replacement therapy of choice for the eligible CKD patients. Readily available methods investigating cardiovascular health help to determine the prognosis in advanced CKD and thus guide treatment.

Elämänlaatu, sydän- ja verisuonitaudit ja kuolleisuus pitkälle edennyttä kroonista munuaistautia sairastavilla Krooninen munuaistauti heikentää elämänlaatua vaikuttaen potilaiden jokapäiväisen elämän lisäksi heidän ennusteeseensa. Sydän- ja verisuonitaudit ovat yleisiä kroonista munuaistautia sairastavilla ja aiheuttavat ylimääräistä kuolleisuutta ja sairastavuutta. Tavanomaisten riskitekijöiden lisäksi krooniseen munuaistautiin liittyvät tekijät lisäävät riskiä. Näiden potilaiden elämänlaadun ja ennusteen parantamiseksi tarvitaan monitahoista hoitostrategiaa. Olisi tärkeää pystyä arvioimaan potilaan ennuste oikein, jotta hoito voitaisiin sovittaa yksilöllisesti. Krooninen valtimotauti, elämänlaatu ja mortaliteetti vaikeaa munuaisten vajaatoimintaa sairastavilla (CADKID) –tutkimukseen osallistui 210 potilasta, joilla oli pitkälle edennyt krooninen munuaistauti mutta ei vielä dialyysihoitoa tutkimuksen alkaessa. Sydäntä ja verisuonistoa tutkittiin rasituskokeella, ultraäänitutkimuksilla ja vatsa-aortan kalkkiutumisen aste (AAC) arvioitiin. Verikokeita tutkittiin laajalti ja elämänlaatua mitattiin. Elämänlaatu oli yhteydessä sydänmerkkiaineisiin troponiini T (TnT) ja B-tyypin natriureettisen peptidin esiaste (proBNP) sekä sydämen systolisen toiminnan mittariin, pitkittäissupistuvuuteen (GLS). Elämänlaatumittarin fyysisen osan yhteen-vetopisteet olivat yhteydessä kuolleisuuteen. Seurantatutkimuksessa munuaissiirto paransi munuaistautiin liittyvää elämänlaatua merkitsevästi verrattuna dialyysiin. CADKID-tutkimuksessa kuolleisuutta ennustivat TnT, proBNP, matala albumiini, AAC, suorituskyky rasituskokeessa ja sydämen diastolisen toiminnan mittari, E/e’. Eteisvärinän esiintyvyys ja ilmaantuvuus oli suurta tutkimusaineistossa. Ikä, koholla oleva TnT ja suurentunut sydämen vasemman eteisen tilavuusindeksi olivat yhteydessä eteisvärinän ilmaantumiseen. Elämänlaatu on yhteydessä sydämen toimintaa kuvaaviin merkkiaineisiin ja ultraäänilöydöksiin. Munuaisensiirto on elämänlaadullisesti paras hoitomuoto loppuvaiheen munuaisten vajaatoimintaan. Yleisesti saatavilla olevilla tutkimuksilla voidaan määrittää potilaan ennuste ja ohjata hoitoa.